Diagnóstico de la inteligencia emocional interpersonal en el desempeño laboral de los servidores públicos del Centro de Salud tipo C del Cantón Chone - Medranda Moreira, Jorge Luis (2020)
The objective of the diagnosis of interpersonal emotional intelligence in the work performance of the Public Servants of the Type C Health Center of Chone canton was to propose activities to improve the interpersonal emotional intelligence of the public servants of the institution. For this, the interview and survey techniques were implemented to obtain the necessary information to carry out the diagnosis, therefore, the use of inductive and deductive methods was decisive in achieving this. Consecutively, once the diagnosis was obtained, the analytical method was implemented, which helped to specify what was the critical area that was found and towards whom the activities that were designed to improve the interpersonal emotional intelligence of each of the the public servants of the Type C Health Center of Chone canton.